An extreme event of enhanced Arctic Ocean export west of Greenland caused by the pronounced dynamic sea level drop in the North Atlantic subpolar gyre in the mid-to-late 2010s. (1st April 2022) - Wang, Qiang; Shu, Qi; Danilov, Sergey; Sidorenko, Dmitry
Abstract: The North Atlantic subpolar gyre influences the climate in many different ways. Here, we identified that it is also responsible for a recent extreme event of Arctic Ocean freshwater export west of Greenland. A shift in climate regimes occurred in the mid-2000s, with a significant negative trend in the dynamic sea level in the subpolar gyre since then. We found that the dynamic sea level drop induced a strong increase in freshwater export west of Greenland, in particular from 2015 to 2017, when the sea level was close to the minimum. Sea ice melting and atmospheric variability in the Arctic had only a small contribution to this event. As the exported water from the Arctic Ocean has low salinity and constituents of chemical tracers very different from those in the North Atlantic, such events might have impacts on the North Atlantic ecosystem and the climate as well. Our study suggests that such events might be predictable if the subpolar gyre sea level has certain predictability.